Impact of surface functionalization on the uptake mechanism and toxicity effects of silver nanoparticles in HepG2 cells. (September 2017) - Brkić Ahmed, Lada; Milić, Mirta; Pongrac, Igor M.; Marjanović, Ana Marija; Mlinarić, Hrvoje; Pavičić, Ivan; Gajović, Srećko; Vinković Vrček, Ivana
Abstract: Safe and successful bioapplications of metallic nanoparticles depend on their physicochemical characteristics, in particular their surface properties. This study aimed to investigate how different surface functionalization of silver nanoparticles (AgNP) affect their interaction with mammalian liver cells with regard to cytotoxicity, genotoxicity and mechanism of cellular uptake. Differentially coated AgNP were prepared by surface functionalization using sodium bis(2-ethylhexyl)-sulfosuccinate (AOTAgNP), cetyltrimethylammonium bromide (CTABAgNP), poly(vinylpyrrolidone) (PVPAgNP), poly- l -lysine (PLLAgNP), and bovine serum albumin (BSAAgNP). Data showed varying toxic potential of differentially coated AgNP. All AgNP types demonstrated concentration dependent effects on cytotoxicity and genotoxicity in HepG2 cells. Cytotoxic potential of differentially coated AgNP followed the order of BSAAgNP > PLLAgNP > CTABAgNP > AOTAgNP > PVPAgNP. Exposure of HepG2 cells to non-cytotoxic concentrations (up to 10 mg Ag/L) of AgNP for 24 h induced primary DNA damage as evaluated by alkaline comet assay. The highest increase in both comet tail length and tail intensity was produced by PLLAgNP followed by AOTAgNP, while CTABAgNP appeared to be least damaging. The main uptake mechanisms of AgNP were macropinocytosis and clathrin-mediated endocytosis. The study findings contribute to the criteria that should be considered in evaluating the biocompatibility and safety of novel nanomaterials. Highlights: Surface functionalization affects cellular toxicity and uptake of silver nanoparticles (AgNP). All AgNP demonstrated dose response cyto- and genotoxicity in HepG2 cells. All AgNP were taken up by macropinocytosis and clathrin-mediated endocytosis.